Analysis of Pending BPJS Claims among Inpatients at RSUP dr. Johannes Leimena Ambon - Setiyono, Dwi Joko; Yayan Mahendroyoko; Puji Lestari, Ita (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Pending claims refer to delays in the payment process of BPJS Kesehatan claims due to administrative, medical, or coding discrepancies. High rates of pending claims affect hospital cash flow and service efficiency. This study aimed to describe the pending claims of BPJS Kesehatan for inpatients at RSUP dr. Johannes Leimena Ambon in 2025 based on their characteristics and causative factors. This quantitative study used a descriptive design with a total sampling of 1,588 pending claim documents from 2025. Data were collected using observation checklists and analyzed descriptively. The results showed that 19% of the total 8,206 claims were pending. The main administrative cause was incomplete referral documents (65%). In the medical aspect, incomplete patient progress notes (64%) were dominant. In coding, the use of non-specific diagnosis codes (92%) was the primary issue. In conclusion, pending claims at this hospital remain high and are driven by systemic issues across administrative, medical, and coding sectors.